On the evaluation of noise immunity of different classes of wideband signals - Evgeny G. Zhilyakov; Sergei P. Belov; Andrei S. Belov; Alexander S. Belov; Sergey A. Rachinsky (Bulletin of Electrical Engineering and Informatics, 2020)
The current stage of the development of the society is characterized by a continuous increase in remote interaction between subscribers and user requests for various types of multiservice services, with the required quality regardless of their location. This is mainly implemented on the basis of wireless communication systems (SBS) at the current time. A large number of various SBSs existing at the present leads to an increase in the level of various types of interference, which makes it necessary to increase the noise immunity of these systems. To improve the reliability of receiving information in the conditions of various types of interference, as is known, it is necessary to implement the information exchange by using channel signals with a large base, which primarily depends on the bandwidth they occupy. In this regard, in the present article, a comparative assessment of the noise immunity is carried out based on the obtained quantitative values of frequency characteristics of a number of modern classes of broadband channel signals, including a new class of broadband channel signals, and the use of eigenvectors of sub-band matrices.